The role of surgery in metastatic squamous cell carcinoma of the penis. Issue 6 (November 2016) - Nicolai, Nicola; Catanzaro, Mario; Zazzara, Michele
Abstract : Purpose of review: Prognosis of penile squamous cell cancer (PeSCC) depends on the involvement of the groin(s) as first step. We introduce the current available evidences that should rule the use of surgery in the management of PeSCC. Recent findings: Prophylactic inguinal node dissection in patients with no palpable nodes associates with immediate and long-term side-effects in up to 70% of patients. Recent findings support selective intervention based on early identification of dynamic sentinel node biopsy (DSNB) with false negative rate of 4–12%. Adequate node retrieval and extending surgery to the pelvis have been addressed as important key factors as staging and therapeutic factors in patients with nodal metastases. Pelvic dissections could be spared only in patients with small (< 3 cm), limited (< 3 nodes) and no extranodal extension. Bilateral pelvic dissection should be recommended in case of involvement of bilateral nodes of at least four. Cisplatin-based neo-adjuvant chemotherapy has a moderate activity, whereas adjuvant chemotherapy associates with prolonged survival in a proportion of patients. Summary: In case of nodal metastases, surgery still represents the most effective treatment. Preventive surgery could be driven by DSNB, which needs an accurate multistep pathway. Extent of surgery is of paramount importance, and inguinal only and unilateral dissections should be reserved to selected patients with the most favorable features. Definitive conclusions concerning perioperative chemotherapy cannot be drawn.